Medication Error Factors, Safety Guideline System, Flow of Drug Use, and Code of Conduct to Prevent Medication Error - Panca, Arvidareyna; Fitriasari, Nikma; Supartiwi, Wiwik (Future Science, 2018)
Medication error is any preventable event that may lead inappropriate drug service or patient harm while the drug administration is in control of the healthcare professional or patient. This study aimed to analyze the factor that may lead the medication error and identify the medication error solution to pharmaceutical installation in research hospital, Indonesia. This study used an action research method. The research subject included doctor, pharmacist, pharmaceutical engineering personnel and nurses. Action research involves six process: diagnosis, reconnaissance, action plan, action, evaluation and monitoring the subject. Diagnosis were obtained from primary and secondary data. Primary data were obtained by interview, observation, and Focus Group Discussion (FGD). Secondary data were obtained from adverse event and near-miss events in medication error data in pharmacy installation. The results indicated that there were four major factor of medication error. First, prescribing error is an unclear written prescription, incomplete administration and unavailable prescription. Second, transcribe error is a misread of prescription drug that lead to mistreatment. Third, dispensing error is involved the misreading of prescription drug by pharmacist, wrong dose, wrong quantity of drugs, and incompetent pharmacist personnel. Fourth, administration error is an incorrect administration by hospital personnel. In conclusion, the establishment of safety guideline is important to medication error in pharmaceutical installation. The safety guidelines consist of the policy and standard operational procedure, flowchart of outpatient service, code of conduct of pharmacy safety and monitoring to ensure the quality of medical service.